2023
DOI: 10.1021/jacs.3c12706
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear-Targeting Lipid PtIV Prodrug Amphiphile Cooperates with siRNA for Enhanced Cancer Immunochemotherapy by Amplifying Pt-DNA Adducts and Reducing Phosphatidylserine Exposure

Dengshuai Wei,
Junning Fan,
Jianqin Yan
et al.

Abstract: Patients treated with Pt-based anticancer drugs (Pt II ) often experience severe side effects and are susceptible to cancer recurrence due to the limited bioavailability of Pt II and tumor-induced immunosuppression. The exposure of phosphatidylserine on the cell's outer surface induced by Pt II results in profound immunosuppression through the binding of phosphatidylserine to its receptors on immune cells. Here, we report a novel approach for enhanced cancer chemoimmunotherapy, where a novel nuclear-targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 49 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…A variety of previous studies have demonstrated that the subcellular localization of a compound inside cancer cells has a drastic effect on its biological effects, including its cytotoxicity, possible interactions with biomolecules, or cell death mechanism. As crucial factors to change the subcellular localization of a compound, researchers have reported on the extension with organelle-targeting moieties, the change of the overall charge or the increase/decrease of the lipophilicity of the compound. , Capitalizing on this, herein, the Pt­(II) anticancer drug cisplatin was modified through axial coordination with aliphatic hydrocarbons or perfluorocarbon carboxylic acids to form Pt­(IV) prodrugs. The axially hydrocarbon carboxylic acid-functionalized metal complexes are followingly referred to as C2–Pt­(IV) , C3–Pt­(IV) , as well as C4–Pt­(IV) and the perfluorocarbon carboxylic acid-functionalized metal complexes are referred to as C2F3–Pt­(IV) , C3F5–Pt­(IV) , as well as C4F7–Pt­(IV) based on the lengths of the extension of the carboxylic acid chain (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of previous studies have demonstrated that the subcellular localization of a compound inside cancer cells has a drastic effect on its biological effects, including its cytotoxicity, possible interactions with biomolecules, or cell death mechanism. As crucial factors to change the subcellular localization of a compound, researchers have reported on the extension with organelle-targeting moieties, the change of the overall charge or the increase/decrease of the lipophilicity of the compound. , Capitalizing on this, herein, the Pt­(II) anticancer drug cisplatin was modified through axial coordination with aliphatic hydrocarbons or perfluorocarbon carboxylic acids to form Pt­(IV) prodrugs. The axially hydrocarbon carboxylic acid-functionalized metal complexes are followingly referred to as C2–Pt­(IV) , C3–Pt­(IV) , as well as C4–Pt­(IV) and the perfluorocarbon carboxylic acid-functionalized metal complexes are referred to as C2F3–Pt­(IV) , C3F5–Pt­(IV) , as well as C4F7–Pt­(IV) based on the lengths of the extension of the carboxylic acid chain (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Chemotherapy is an essential therapy for tumors that can inhibit various types of solid and nonsolid tumors. However, some chemotherapy drugs, such as platinum-based drugs, have defects such as low bioavailability and severe side effects. To address these deficiencies, many nanomaterials have been utilized as carriers to load platinum drugs. Despite this, there is still a lack of research on the mechanism of action of these nanomedicines, which adversely affects their further clinical translation. To solve this problem, Wang et al used RNA-seq and metabolomics to study the mechanism of nanobased platinum drugs.…”
Section: Application Of Nanomedomicsmentioning
confidence: 99%
“…Pt­(IV) complexes, commonly exhibiting an octahedral structure, are characterized by their high chemical inertness that results in fewer side effects than Pt­(II) drugs by reducing unfavorable interactions with biomolecules . Upon cellular uptake, inert Pt­(IV) prodrugs can be reduced to highly active Pt­(II) and exhibit cytotoxicity. , In the field of cancer therapy, nanodrug delivery systems have garnered significant attention as they endow small-molecule drugs with tumor-targeting properties due to the enhanced permeability and retention (EPR) effect. , However, the effectiveness of the EPR effect heavily relies on tumor characteristics, necessitating the implementation of more sophisticated drug delivery strategies, such as reduction-responsive polymers, to improve tumor uptake. Considering that the concentration of glutathione (GSH) in tumor cells is significantly higher than that in blood and normal cells, the disulfide bond, which can offer on-demand drug release via fast cleavage in a reducing tumor environment, has been frequently employed in the creation of reduction-responsive polymers. , Recent investigations have revealed that the trisulfide bond, in comparison to the conventional disulfide bond, exhibits improved stability in the presence of low levels of GSH and a blood pool. However, it displays extreme susceptibility to excessive GSH in tumor cells, , thereby demonstrating greater selectivity.…”
mentioning
confidence: 99%